Prohibited Mountains and Forests in Late Imperial China - Vincent Goossaert (Religions)
This essay explores the various types of spaces, primarily montane forested areas, where human access was restricted, either conditionally or entirely, during late imperial times. The range of restrictions always included felling trees, but often also encompassed other forms of extraction from local ecosystems. Based on the motivations for setting up and regulating such zones, it proposes a typology that includes imperial parks and graves, sacred sites, military exclusion zones, and certain forested commons. Based on some commonalities between these types, it concludes by reflecting on the place of notions of sacrality in local policies that directly impacted forested areas.